Pengembangan Mobile Learning Management System Dengan User Centered Design (UCD) Menggunakan Flutter Framework - Condro Kartiko; Ariq Cahya Wardhana; Diovianto Putra Rakhmadani (STMIK Budi Darma, 2022)
The Learning Management System is a supporter of online learning management so that the teaching and learning process remains quality like face-to-face. This study aims to develop a mobile learning management system application using the flutter framework for students at the Telkom Purwokerto Institute of Technology with the User Centered Design method. This research creates a mobile-based Learning Management System that can be accessed and functions according to the needs of users, namely students. The application test results show that all functions run according to user needs so that this system can help make online learning easier via smartphones.